1934
DOI: 10.1042/bj0281993
|View full text |Cite
|
Sign up to set email alerts
|

The significance of phosphatase estimations in the adult fowl

Abstract: KAY [1930] showed that in certain bone diseases in man the plasma-phosphatase activity is considerably higher than normal. This served as an impetus for investigation into the activity of the enzyme in plasma and tissues under different conditions in man and experimental animals. The literature has been reviewed by Kay [1932] and by Robison [1932], and it is unnecessary to go into it in great detail here. Briefly, it may be said that in healthy young animals the activity of the plasma-phosphatase is higher tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

1936
1936
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…Similar comparisons for birds at 16 months of age, however, show no significant difference between plasma and whole blood, in fact, plasma phosphatase values were often slightly lower than those of whole blood. This tendency in the younger birds for the plasma to have a higher phosphatase value than whole blood is interesting in view of the work of Auchinachie and Emslie (1934) who found no significant difference when comparisons were made of the phosphatase activity of oxalated blood plasma, "native" plasma, and serum. These porkers, however, did not include whole blood in their studies.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Similar comparisons for birds at 16 months of age, however, show no significant difference between plasma and whole blood, in fact, plasma phosphatase values were often slightly lower than those of whole blood. This tendency in the younger birds for the plasma to have a higher phosphatase value than whole blood is interesting in view of the work of Auchinachie and Emslie (1934) who found no significant difference when comparisons were made of the phosphatase activity of oxalated blood plasma, "native" plasma, and serum. These porkers, however, did not include whole blood in their studies.…”
mentioning
confidence: 90%
“…In view of the wide normal range of plasma phosphatase in adult birds reported by Common (1934Common ( ,1936 and Auchinachie and Emslie (1934), it would appear that any study designed to determine the fac- tors responsible for these variations would be a valuable and necessary preliminary to subsequent vitamin and mineral metabolism studies. In this paper data on phosphorus and phosphatase levels of the plasma and whole blood of male and female birds at 5 and 16 months of age are presented.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Auchinachie & Emslie (1934) and Gutowska et al (1943) found somewhat higher levels of phosphatase in the small white ovules (immature white follicles) and the ovary than in the oviduct, but only a trace of the enzyme in the large ova. However, a high phosphatase level is present in the follicle membrane of large ova (Abe, Kaneko, Otsuka 8c Hosoda, 1962).…”
Section: Introductionmentioning
confidence: 99%
“…Alkaline phosphatase has been shown to be present in all regions of the oviduct by various workers (Auchinachie & Emslie, 1934;Gutowska, Park-hurst, Parrot & Verbürg, 1943;Sanz & Lorenzo, 1950;Brown & Badman, 1962), although at rather low levels. Auchinachie & Emslie (1934) and Gutowska et al (1943) found somewhat higher levels of phosphatase in the small white ovules (immature white follicles) and the ovary than in the oviduct, but only a trace of the enzyme in the large ova.…”
Section: Introductionmentioning
confidence: 99%